Developing Competencies in a Mechanism Course Using a Project-Based Learning Methodology in a Multidisciplinary Environment - Alejandro Guajardo-Cuéllar; Carlos Renato Vázquez; Manuel Navarro Gutiérrez (MDPI AG, 2022)
Design of Mechanism is a standard subject in Mechatronics and Mechanical Engineering majors. Different methods and tools are used by lecturers to teach the subject. In this work, we investigate the impact on the competencies development by implementing a project-based learning methodology in a mechanism course. For this, we analyze the performance of students from two different groups. The first group is taught in a traditional fashion developing a final project just related to the discipline, and the second group is taught in a multidisciplinary context where the final goal is to develop a complex project where the mechanisms subject is one complementary subject with the others. The development of engineering competencies, declared for this course, is presented for both groups through the evaluation of different aspects; also, a survey of satisfaction from the students of both groups is presented. Overall, the results show that the multidisciplinary project-based learning method, having a nonacademic training partner as sponsor and solving a real nonacademic project, improves the development of competencies related to practical applications and increases the motivation and appreciation of the student towards the mechanism learning discipline.